Peningkatan Kompetensi Guru dalam Pengelolaan Pembelajaran di Kelas - Lubis, Syakwan (Pusat Kajian Civics Fakultas Ilmu-ilmu Sosial Universitas Negeri Padang, 2011)
Implementation of Competency-Based Curriculum in 2004, known as KBK, which was followed by the Education Unit Level Curriculum in 2006, known as KTSP, has demanded an increase of teacher quality. This of course implies that eventually every school educational institutions in great need of qualified teachers and adequate in carrying out their duties at school. Therefore the implementation of the curriculum can be run as expected by many, then there needs to be upgraded on the ability of teachers. This article will try to discuss the improving teacher competency in Classical Learning Management according to the purposes of the two curriculums.Kata Kunci: Kompetensi, pengelolaan pembelajaran, kurikulum berbasis kompetensi, pengelolaan kelas